2014
DOI: 10.1097/01.ehx.0000455682.80650.e
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical study on the effect of aflatoxin B1 on the left ventricular muscle of adult male rabbit with reference to the protective role of melatonin

Abstract: These findings proved that AFB1 has adverse effects on the left ventricular muscles of rabbits, which were ameliorated by coadministration of MEL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…These results are in agreement with previous studies that reported degenerative changes in the rat cerebral cortex and in the cerebellum (Iwanowski, 1988;Ratan et al, 1994). Congestion and dilatation of cerebral, cerebellar and myocardial blood vessels were also reported after chronic exposure to different doses of aflatoxin (Ikegwuonu, 1983;Laag and Abd el Aziz, 2013;Soliman and Tawfik, 2014). The effect on the blood vessels can be attributed to the stimulating effect of aflatoxin on endothelial relaxation factors, such as nitric oxide, (Mannaioni et al, 1997;Wang et al, 2001) and to the toxic effect of AFB1 on the brain microvascular endothelial cells which constitute the blood-brain barrier (Qureshi et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with previous studies that reported degenerative changes in the rat cerebral cortex and in the cerebellum (Iwanowski, 1988;Ratan et al, 1994). Congestion and dilatation of cerebral, cerebellar and myocardial blood vessels were also reported after chronic exposure to different doses of aflatoxin (Ikegwuonu, 1983;Laag and Abd el Aziz, 2013;Soliman and Tawfik, 2014). The effect on the blood vessels can be attributed to the stimulating effect of aflatoxin on endothelial relaxation factors, such as nitric oxide, (Mannaioni et al, 1997;Wang et al, 2001) and to the toxic effect of AFB1 on the brain microvascular endothelial cells which constitute the blood-brain barrier (Qureshi et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Also, it is found that Aflatoxin produces reactive oxygen species (ROS), which induce inflammatory process by formation of Tumor necrosis factor (TNF-α) and cytokines that attract leukocytes and other inflammatory cells into lesion site as a protection mechanism to eliminate injured tissue. This is confirmed by E.M. findings in GIII [27] .…”
Section: Discussionsupporting
confidence: 85%
“…So, AFs have damaging effects on cells specially ileum because its high protein turnover [28] . Furthermore, collection of reactive free radicals releases lysosomal enzymes into the cytosol which lead to oxidation and lysis of the protein [27] . By using transmission electron microscope, in GIII damaged absorptive columnar cells and M cells (which can be considered differentiated form of absorptive columnar cells [29] ) show shrinkage of their nuclei, interrupted intracellular junctions' complexes, loss of terminal webs and lost damaged microvilli [18] .…”
Section: Discussionmentioning
confidence: 99%
“…One common finding in this work was interrupted intercalated disc (ICD) that have been documented in other researches [30] and was explained by mitochondrial damage that caused depletion of ATP production and activation of phospholipase enzyme leading to breakdown of the phospholipids. This resulted in abnormality of lipid peroxidation of the sarcolemma and internal membranes leading to loss of the control of ions permeability and a subsequent abnormality in the membrane structure which could explain the irregular sarcolemma found in the present study [31] . Koeppen et al, [32] have proposed another possible explanation of ICD abnormality to be due to changes in the molecular proteins of the junctions present within the ICD as N-cadherin, vinculin and desmosomal protein desmoglein 2 as well as abnormal distribution of the connexin 43 protein within the gap junction.…”
Section: Discussionmentioning
confidence: 58%